A cross-sectional study on schistosomiasis and soil-transmitted helminths in Mbita district, western Kenya using different copromicroscopic techniques. Issue 1 (December 2016) - Ng'etich, Annette; Rawago, Fredrick; Jura, Walter; Mwinzi, Pauline; Won, Kimberly; Odiere, Maurice
Abstract Background Identification of populations to be targeted for individual treatment and broad-spectrum therapy in schistosomiasis-endemic areas, assessment of therapy efficacy, morbidity, and evaluation of control strategies need to be based on reliable diagnostic tools. Kato-Katz is routinely used and remains the standard diagnostic technique for schistosomiasis, despite its many challenges. This study was conducted in Nyamanga village, Mbita, western Kenya, and evaluated the diagnostic performance of Kato-Katz, Mini-Parasep and modified Mini-FLOTAC techniques in detection ofSchistosoma mansoni and soil-transmitted helminths (Ascaris lumbricoides, Trichuris trichiura and hookworm) ova. Methods Stool samples from 132 individuals were screened for eggs ofS. mansoni by the 3 techniques. Mini-Parasep® faecal parasite concentrator (Apacor Ltd, England), a single-use diagnostic device with a built-in filter for faecal concentration of helminth eggs by sedimentation was employed on stool samples fixed in 10 % formalin. A modified Mini-FLOTAC (University of Naples, Italy) was based on floatation of helminths eggs with two different solutions (FS2 and FS7) using a closed system (Fill-FLOTAC) with 5 % formalin. Kato-Katz was performed following WHO recommendation. Prevalence ofS. mansoni and STH, sensitivity and degree of agreement among the 3 techniques were determined. Results Prevalence ofS. mansoni was 47.0 %, 34.1 % and 20.5 % by Mini-Parasep, Kato-Katz and modified Mini-FLOTAC FS7 techniques, respectively. Prevalence of any STH infection was 6.1 %, 3.0 %, 6.1 % and 6.8 % by Mini-Parasep, Kato-Katz, modified Mini-FLOTAC FS2 and modified Mini-FLOTAC FS7 techniques, respectively. Considering the pooled results of the three methods (Mini-Parasep, Kato-Katz and modified Mini-FLOTAC FS7) as diagnostic 'gold' standard, the sensitivity of Mini-Parasep, Kato-Katz and modified Mini-FLOTAC FS7 forS. mansoni was 77.5 %, 56.1 %, and 33.8 %, respectively. Mini-Parasep and modified Mini-FLOTAC FS7 techniques had moderate (κ = 0.46) and fairly good (κ = 0.25) agreements with Kato-Katz forS. mansoni, respectively. Mini-Parasep detected a higher proportion of light intensityS. mansoni infections compared to Kato-Katz, which detected high proportions of heavy infections. Mini-Parasep detected a similar mean number ofS. mansoni eggs per gram (EPG) of stool compared to the standard Kato-Katz (62.9 vs 97.3; t(131) = -0.49, P = 0.6265) and significantly higher EPG compared to the modified Mini-FLOTAC FS7 (62.9 vs 34.6; t(131) = 5.39, P < 0.0001). Conclusions The high sensitivity of Mini-Parasep suggests its promising potential as an alternative tool in enhancing diagnosis and in monitoring schistosomiasis transmission and determining endpoint of intervention programs, especially in low endemicity areas. Mini-Parasep is also easy to operate, safe and also permits work with fresh stool.